Public policy and governance in India: The politics of implementation - Yadav, Sushma (2010)
Policy implementation is of keen importance to the success of a government. Even if the political system is fair, even if the goals are noble and even if the organizational structure isvery strong, no policy can succeed if the implementation part is not up to the mark. The implementation of government policies and programmes is now playing a vital role in the developmental strategy. However, there are studies to show that the implementation aspect is the most neglected, which makes a study of the institutions that make policy as much as those who implement them all the more important. Measured by economic growth or attainment of human development objectives, India remains not only an underdeveloped country but one which is usually regarded as an under-performer, which could do better. If it is accepted, the question then arises as to why be this case. Was the policy adopted by the state not right? Or was it not implemented properly? Or was the political commitment and support for the desired course of action lacking? The paper seeks to probe these and related issues and also looks at possible reforms. - Reproduced.
Keywords: Good governance - India; Public policy - India; Public policy